Modeling of Seasonal Lake Level Fluctuations of Titan's Seas/Lakes - Tokano, Tetsuya; Lorenz, Ralph D. (AMER GEOPHYSICAL UNION, 2019)
Seasonal variations in lake levels of Titan's hydrocarbon seas/lakes are predicted by an ocean circulation model in an effort to understand the observed temporal changes in lake size or lack thereof. Three different ground permeabilities are assumed so as to change the relative importance of precipitation, evaporation, river runoff, and groundwater seepage for the lake methane budget. The lake level generally rises in the rainy season around the summer solstice and falls or stagnates during long dry periods in autumn and winter. The annual lake level range in the northern hemisphere amounts to 50-120cm depending on geographic location and size of the lakes and ground permeability. If the hydraulic connection between Punga Mare and Kraken Mare is weak, the lake level range of Punga Mare amplifies at the expense of other seas and also establishes a large lake level difference between these two seas, which is not compatible with the observation by the Cassini spacecraft. On-lake precipitation would cause the lake level of Ontario Lacus to vary seasonally by merely 15 cm, yet river runoff from the huge catchment area can increase the annual lake level range to several meters. The shrinkage of Ontario Lacus observed by Cassini is more likely to be caused by lakebed seepage than by evaporation. The ultimate cause of the difference in the seasonal behavior between northern and southern lakes may be the hemispheric asymmetry in precipitation, be it caused astronomically or topographically. Plain Language Summary Saturn's moon Titan has many hydrocarbon lakes in the polar region, but only one lake near the south pole has so far shown evidence of lake size change. In order to understand the possible difference in the temporal variation between the northern and southern lakes, we simulated numerically the seasonal lake level change of all major lakes on Titan. The lake level generally rises in spring and summer during the rainy season and falls in dry seasons due to evaporation. However, the magnitude of lake level ...